Life cycle assessment of intensified processes towards circular economy: Omega-3 production from waste fish oil - Monsiváis-Alonso, Rafael; Mansouri, Seyed Soheil; Román-Martínez, Alicia (Chemical engineering and processing, 2020)
[Display omitted] •A framework for lipid process design in a Circular Economy model was developed.•The case study addressed was the production of ω-3 concentrates from waste fish oil.•The multiobjective optimization problem includes intensified process options•The resulting MINLP is solved with lexicographic, ε-constraint and LCA approaches.•The optimal process configuration counterbalances the three sustainability dimensions. Fish oil is a nutritious product, mainly due its omega-3 polyunsaturated fatty acids (ω-3 PUFA) content that is attractive for its health benefits. Fish oil is discarded as a waste in many seafood industries, due to the lack of recovery processes to refine the oil in a lucrative and sustainable manner. This work tackles this by proposing a framework to integrate the economic, environmental and social aspects with the process design decisions of a crude fish oil refinery. The application of the framework is highlighted through production of ω-3 PUFA concentrates from waste oil of a tuna processing plant in Mexico. This is addressed by formulation and solution of a multi-objective optimization problem including intensified processing options in a superstructure. The resulting Mixed Integer Non-Linear Programing problem is solved with lexicographic and ε-constraint methods. The solutions in the form of a Pareto front are subject to benchmarking with Life Cycle Assessment (LCA) methodology. The optimal configuration consists of an intensified process with an LCA score of 458.94 and the donation 12.64 % of the ω-3 production to local communities without compromising the process profitability. Waste fish oil valorization is proven significant to achieve a circular economy model for the seafood industry.